2017
DOI: 10.3389/fmicb.2017.02137
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Composition and Functional Capacity in a Terrestrial Ferruginous, Sulfate-Depleted Mud Volcano

Abstract: Terrestrial mud volcanoes (MVs) are an important natural source of methane emission. The role of microbial processes in methane cycling and organic transformation in such environments remains largely unexplored. In this study, we aim to uncover functional potentials and community assemblages across geochemical transitions in a ferruginous, sulfate-depleted MV of eastern Taiwan. Geochemical profiles combined with 16S rRNA gene abundances indicated that anaerobic oxidation of methane (AOM) mediated by ANME-2a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 74 publications
2
35
0
Order By: Relevance
“…Their increase (ca. 5%) in relative 16S rRNA gene sequence abundance over 250 days is in tandem with the observed iron reduction detected by measuring dissolved iron over time (Supplementary Figure S8), and thus, they might serve as potential iron oxide-reducing partner bacteria in AOM (Chang et al, 2012;Tu et al, 2017). Besides the Desulfuromonadales, unclassified Gammaproteobacteria were highly stimulated compared to day 0 across all incubations in both geochemical zones (Supplementary Figure S9).…”
Section: Microbial Key Players Involved In Fe-aomsupporting
confidence: 58%
See 2 more Smart Citations
“…Their increase (ca. 5%) in relative 16S rRNA gene sequence abundance over 250 days is in tandem with the observed iron reduction detected by measuring dissolved iron over time (Supplementary Figure S8), and thus, they might serve as potential iron oxide-reducing partner bacteria in AOM (Chang et al, 2012;Tu et al, 2017). Besides the Desulfuromonadales, unclassified Gammaproteobacteria were highly stimulated compared to day 0 across all incubations in both geochemical zones (Supplementary Figure S9).…”
Section: Microbial Key Players Involved In Fe-aomsupporting
confidence: 58%
“…In terrestrial mud volcanoes where Fe-AOM is also suggested to occur, high correlation between gene copies of Desulfuromonadales and ANME-2a was taken as indication for ANME-2a to oxidize methane with Desulfuromonadales as iron oxide reducing partners (Chang et al, 2012;Tu et al, 2017). While dissimilatory iron oxide reducers (e.g., Desulfuromonadales) have not been clearly shown to act as partners for ANMEs, the increased relative abundance of Desulfuromonadales 16S rRNA genes (Figure 5B) cannot be ignored.…”
Section: Anme-2a Identified As Key Player Involved In Fe-aommentioning
confidence: 99%
See 1 more Smart Citation
“…Although these primers have been reported to be less efficient in generating archaeal amplicons (Parada et al 2016), they were used to facilitate the comparison with other studies. The schemes and reagents for PCR and downstream processing of amplicons were the same as those described in Tu et al (2017).…”
Section: Dna Extraction and 16s Rrna Gene Analyzesmentioning
confidence: 99%
“…At hydrothermal vents, chemolithoautotrophs initiate the microbial trophic network and proliferate at high rates leading to high microbial cell numbers 1 . While volcanic sites and hydrothermal vent fields have been studied fairly thoroughly regarding their microbiome and the microbial activity 25,26,27,28,29 , little is known about deep subsurface ecosystems with low temperatures but heavy impact from gases released from the mantle.…”
Section: Introductionmentioning
confidence: 99%